2012
DOI: 10.1126/science.1227037
|View full text |Cite
|
Sign up to set email alerts
|

Salmonella Inhibits Retrograde Trafficking of Mannose-6-Phosphate Receptors and Lysosome Function

Abstract: Salmonella enterica is an intracellular bacterial pathogen that replicates within membrane-bound vacuoles through the action of effector proteins translocated into host cells. Salmonella vacuoles have characteristics of lysosomes but are reduced in hydrolytic enzymes transported by mannose-6-phosphate receptors (MPRs). We found that the effector SifA subverted Rab9-dependent retrograde trafficking of MPRs, thereby attenuating lysosome function. This required binding of SifA to its host cell target SKIP/PLEKHM2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
161
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 177 publications
(166 citation statements)
references
References 31 publications
5
161
0
Order By: Relevance
“…4C). Both the sifA single mutant and the sifAsseJ double mutant are deficient in the inhibition of lysosome fusion, but only the sifA single mutant "escapes" the SCV and resides in the cytosol (24). Therefore, these results clearly suggest that cytosolic bacteria experience more redox stress than bacteria that reside inside the SVC.…”
Section: An Intact Salmonella-containing Vacuole Is Essential For Rosmentioning
confidence: 51%
See 2 more Smart Citations
“…4C). Both the sifA single mutant and the sifAsseJ double mutant are deficient in the inhibition of lysosome fusion, but only the sifA single mutant "escapes" the SCV and resides in the cytosol (24). Therefore, these results clearly suggest that cytosolic bacteria experience more redox stress than bacteria that reside inside the SVC.…”
Section: An Intact Salmonella-containing Vacuole Is Essential For Rosmentioning
confidence: 51%
“…It is known that from inside the SCV, S. Typhimurium regulates fusion with vesicles through the actions of SPI-2 effectors. For example, SPI-2 effector SifA directs trafficking of mannose-6-phospate receptors and thereby inhibits lysosome function (24). Additionally, SifA is implicated in maintaining the integrity of the SCV, and it is well documented that infection with the sifA mutant leads to loss of SCV integrity (25).…”
Section: An Intact Salmonella-containing Vacuole Is Essential For Rosmentioning
confidence: 99%
See 1 more Smart Citation
“…Rab11 isoforms and their downstream effectors have critical roles in cell polarity, and defects underlie cancer, gastrointestinal, and degenerative disease (for reviews, see Jing and Prekeris 2009;Kelly et al 2012;Mitra et al 2012). Rab9 regulates the recycling of cargo (mannose-6-phosphate receptor) from late endosomes to the Golgi complex (Lombardi et al 1993;McGourty et al 2012;Dong et al 2013). The described GTPases contribute to the functional endosomal compartmentalization and cargo transport to early endosomes, plasma membrane, and Golgi recycling, and transport to degradation.…”
Section: Rab Gtpases On the Endocytic Pathway Compartmentalize Endocymentioning
confidence: 99%
“…Preliminary evidence has indicated that several pathogens, such as Shigella, Salmonella, Mycobacteria, and influenza A virus, have evolved mechanisms that evade the autophagic response. [8][9][10][11] B. pseudomallei has the capacity to invade a number of cultured mammalian cell lines. 4 After entry, B. pseudomallei utilizes numerous strategies that enable it to survive in such a specialized niche as the intracellular environment.…”
Section: Introductionmentioning
confidence: 99%